STUDENT SELF-TESTS AND INTERACTIVE QUIZZES FOR IMPROVING PSYCHIATRY SUMMATIVE ASSESSMENT ACHIEVEMENT - Firdaus Firdaus; Winarto Winarto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Formative assessment is an important assessment in medical education. Formative assessment strengthens the learning process, consolidates learning materials, strengthens learning behavior and improves student performance in learning. Formative assessment must have a place in the student assessment regulatory system to increase educational outcomes. Formative assessment needs to be continuously developed, especially assessment as learning to encourage student participation in monitoring the process and progress of their learning. This study aims to determine whether the application of self-tests and interactive quizzes created by students can improve summative exam results. In particular, it aims to determine the relationship between the results of the self-test developed by students with the results of summative assessment, and to find out whether there are differences in summative assessment results between the group that took the self-test and received the interactive quiz with the group that did not take the self-test and did not get the interactive quiz.Methods: This study was a cross sectional experimental study. Number of samples was 174 people, consisting of 87 intervention groups and 87 control groups. The sample was selected using disproportionate stratified random sampling.Results: The results of the self-test and the summative assessment results showed a significant relationship with sig (2-tailed) of 0.000, the Pearson correlation coefficient 0.563, indicating a strong relationship. The result of the summative assessment, the intervention group was 70.54 significantly higher than that of the control group 64.13. Analysis of differences using the independent T Test sig 0.000.Conclusion: Student self-tests and interactive quizzes have been proven to improve student summative exam results in learning block psychiatry.